Interaction between RB protein and NuMA is required for proper alignment of spindle microtubules. (19th December 2013) - Uchida, Chiharu; Hattori, Takayuki; Takahashi, Hirotaka; Yamamoto, Naoki; Kitagawa, Masatoshi; Taya, Yoichi
<x xml:space="preserve">Abstract</x> Retinoblastoma protein (pRB) controls cell cycle progression and cell cycle exit through interactions with cellular proteins. Many pRB‐binding proteins, which function in gene transcription or modulation of chromatin structure, harbor LXCXE motifs in their binding domain for pRB. In this study, we found that nuclear mitotic apparatus protein (NuMA), a mitotic spindle organizer, interacts with pRB through LSCEE sequences located in its C‐terminal region. siRNA‐mediated down‐regulation of pRB caused aberrant distribution of NuMA and alignment of spindle microtubules in mitotic cells. Abnormal organization of spindle microtubules was also accompanied by misalignment of an over‐expressed NuMA mutant (mut‐NuMA) with a defect in pRB binding caused by an LSGEK mutation. The mut‐NuMA‐over‐expressing cells showed lower potency for survival than wild‐type NuMA (wt‐NuMA)‐over‐expressing cells during 2 weeks of culture. Interestingly, knockdown of pRB reduced the population of wt‐NuMA‐over‐expressing cells to the same level as mut‐NuMA cells after 2 weeks. Taken together, pRB may have a novel function in regulating the mitotic function of NuMA and spindle organization, which are required for proper cell cycle progression.